2016
DOI: 10.1289/ehp147
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Persistent Organic Pollutants and Insulin Secretion among Children Age 7–9 Years: A Prospective Cohort Study

Abstract: Background:Persistent organic pollutants (POPs) are endocrine disruptors and have been suggested as possible risk factors for diabetes. Few studies have been performed to investigate this association among children.Objectives:In this study, we prospectively examined the relationship between the serum concentration of POPs and glucose metabolism in children.Methods:Data were collected from the Ewha Birth & Growth Cohort Study, an ongoing birth cohort study initially constructed between 2001 and 2006. In 2010–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Although epidemiological and experimental studies have revealed the relationship of POPs with IR (6,7), some human studies have suggested that direct toxicity of POPs to b-cells (rather than to decreased peripheral insulin sensitivity) may be a more plausible mechanism linking POPs and T2D (8)(9)(10). For example, serum concentrations of POPs were related to the markers of b-cell dysfunction (e.g., HOMA-b and 2-h insulin after oral glucose tolerance test [OGTT]), not IR markers among Greenland Inuit without diabetes (9).…”
mentioning
confidence: 99%
“…Although epidemiological and experimental studies have revealed the relationship of POPs with IR (6,7), some human studies have suggested that direct toxicity of POPs to b-cells (rather than to decreased peripheral insulin sensitivity) may be a more plausible mechanism linking POPs and T2D (8)(9)(10). For example, serum concentrations of POPs were related to the markers of b-cell dysfunction (e.g., HOMA-b and 2-h insulin after oral glucose tolerance test [OGTT]), not IR markers among Greenland Inuit without diabetes (9).…”
mentioning
confidence: 99%
“…Quality control serum samples were incorporated in each batch of 15 samples. The recoveries of the internal standards were satisfactory, in general ranging from 50 to 120% (Park et al, 2016). The relative standard deviation of the quality assurance/quality control (QA/QC) samples was <15% for all compounds that were presented above the limit of detection (LOD) in the QA/QC samples.…”
Section: Persistent Organic Pollutants Analysesmentioning
confidence: 92%
“…The detailed methodology of the POPs analyses was described previously (Park et al, , 2016. Isotopic substitution method was used in this study (U.S. EPA, 1994;Dmitrovic et al, 2002;Muir and Sverko, 2006).…”
Section: Persistent Organic Pollutants Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we will therefore focus on BPA and phenols when referring to EDCs. [6][7][8][9][10] The association between BPA and T2DM has been investigated in both epidemiological and animal studies. [11][12][13] There is, however, a dearth of studies examining the association between phenols and other EDCs and GDM.…”
mentioning
confidence: 99%